2020
DOI: 10.1002/adhm.201901608
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Magnetically Levitated Plasma Proteins Detects Opioid Use Disorder as a Model Disease

Abstract: There are several methods (e.g., enzyme‐linked immunosorbent assay and liquid chromatography mass spectroscopy) that already use human plasma to detect a variety of possible diseases. However, this paper introduces the capabilities of magnetic levitation (Maglev) to detect disease (Opioid Use Disorder, used here as a model disease) by using levitation of human plasma proteins. The presented proof‐of‐concept findings revealed that the optical images of magnetically levitated plasma proteins carry important info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…We have recently levitated plasma proteins using superparamagnetic iron oxide nanoparticles and revealed that the levitated plasma proteins create ellipsoidal patterns [238]. Using machine learning and liquid chromatography mass spectroscopy approaches, we then demonstrated that the patterns of the levitated plasma proteins contain useful information regarding the health spectrum of plasma donors [239]. This strategy can be very helpful and feasible for monitoring the interactions between gut microbiota patterns and CAD.…”
Section: Microbiota and Nanomedicine-based Approachesmentioning
confidence: 99%
“…We have recently levitated plasma proteins using superparamagnetic iron oxide nanoparticles and revealed that the levitated plasma proteins create ellipsoidal patterns [238]. Using machine learning and liquid chromatography mass spectroscopy approaches, we then demonstrated that the patterns of the levitated plasma proteins contain useful information regarding the health spectrum of plasma donors [239]. This strategy can be very helpful and feasible for monitoring the interactions between gut microbiota patterns and CAD.…”
Section: Microbiota and Nanomedicine-based Approachesmentioning
confidence: 99%
“…59 Specifically, our supervised classification analysis demonstrated proof-of-concept that the movement of levitating proteins in MagLev has disease detection capacity, with potential use in a point-of-care device. 59 More specifically, we found that MagLev optic images of levitated proteins, subjected to machine-learning analysis, offer valuable information on the individual's health status ( Figure 4). 59 In addition, the levitated ellipsoidal patterns of proteins can be separated and analyzed with proteomic approaches to learn more about the role of important proteins in disease development.…”
Section: ■ Biomolecular Coronamentioning
confidence: 90%
“…59 More specifically, we found that MagLev optic images of levitated proteins, subjected to machine-learning analysis, offer valuable information on the individual's health status ( Figure 4). 59 In addition, the levitated ellipsoidal patterns of proteins can be separated and analyzed with proteomic approaches to learn more about the role of important proteins in disease development. 59 Based on these results, the MagLev platform may have the capacity for rapid discrimination of patients at risk of fatal COVID-19 progressive disease (e.g., by exacerbating cardiovascular diseases 3−5 ) and also accelerate the development of biomarker(s) to identify such patients.…”
Section: ■ Biomolecular Coronamentioning
confidence: 96%
See 1 more Smart Citation
“…However, oil and some surfactants are inevitably used in the preparation process, as a result, microspheres often lack good biocompatibility. [ 30,31 ] Emulsion method faces the similar problem. This has become the main factor restricting the further development of microfluidic and emulsion technology.…”
Section: Introductionmentioning
confidence: 99%